2006
DOI: 10.1074/jbc.m509530200
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Sterol Structural Specificity

Abstract: Desmosterol is an immediate precursor of cholesterol in the Bloch pathway of sterol synthesis and an abundant membrane lipid in specific cell types. The significance of the difference between the two sterols, an additional double bond at position C24 in the tail of desmosterol, is not known. Here, we provide evidence that the biophysical and functional characteristics of the two sterols differ and that this is because the double bond at C24 significantly weakens the sterol ordering potential. In model membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 53 publications
7
56
0
Order By: Relevance
“…This would require large scale preparation of immunoisolated caveolae from 20,25-DAC-treated versus untreated animals, for example. The C24 double bond gives rise to additional stress in the sterol tail, favors tilting of the molecule in the bilayer (13), and may thereby sterically hinder interactions with Cav1. The reduced sterol affinity may, in turn, explain the reduced association of Cav1 with DRMs as well as the decreased stability of caveolin oligomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would require large scale preparation of immunoisolated caveolae from 20,25-DAC-treated versus untreated animals, for example. The C24 double bond gives rise to additional stress in the sterol tail, favors tilting of the molecule in the bilayer (13), and may thereby sterically hinder interactions with Cav1. The reduced sterol affinity may, in turn, explain the reduced association of Cav1 with DRMs as well as the decreased stability of caveolin oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the accumulation of desmosterol, which differs from cholesterol by an additional double bond between carbon atoms 24 and 25 in the sterol tail. We chose this strategy as data on DHCR24-deficient mice (11, 12) and on cultured cells containing desmosterol (13,14) suggested that desmosterol accumulation may specifically interfere with the function of proteins enriched in lipid rafts/caveolae. Our results show that the minor structural difference between cholesterol and desmosterol weakens sterol-caveolin interaction, results in distorted caveolae with an altered number of Cav1 molecules per caveola, and affects the function of caveolae as endocytic vehicles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rafts have been suggested to participate in a wide range of cellular processes such as trafficking and sorting of proteins. Recent atomistic simulations of lipid rafts 8,9 and other lipid bilayer systems including cholesterol and other sterols 10,[14][15][16] have provided insight into the atomicand molecular-scale interaction mechanisms of the raftassociated lipids. However, to reach the length and time scales necessary to study large-scale phenomena, one has to resort to coarse-grained models that employ effective interactions and simplify the description of the underlying system.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is oriented in the bilipid membrane with its hydrocarbon tail at the interface of the outer and inner leaflets. The double bond in des- mosterol causes greater tilt in the sterol structure that results in decreased membrane lipid packing and ordering, thus altering membrane properties such as fluidity (27). Desmosterol's effect on membrane architecture may adversely influence the membrane flexibility necessary for membrane fusion.…”
mentioning
confidence: 99%